Desalination using spray tower and vapour compression refrigeration system. (12th April 2006) - Sathish Kumar, S.; Mani, A.
A desalination system using a spray tower and Vapour Compression Refrigeration (VCR) system is proposed for obtaining fresh water from brackish water. In the spray tower, simultaneous heat and mass transfer take place between the brackish water and air, which results in the evaporation of the brackish water and humidification of the air. Fresh water is obtained from the humidified air by condensing the water vapour using a VCR system. Parametric studies were carried out to study the effect of various operational parameters on the fresh water production rate.